1954
DOI: 10.1007/bf02158515
|View full text |Cite
|
Sign up to set email alerts
|

Konstitution des Aldosterons, des neuen Mineralocorticoids

Abstract: Volumen XXXYII, Fasciculus IT (1964) -So. 137-1 38. 138. Aldosteron. Isolierung und Eigenschaften. ober Bestandteile der Nebennierenrinde und verwandte Stoffe. 91. Mitteilung1)2) voii S

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
1
4

Year Published

1956
1956
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(45 citation statements)
references
References 6 publications
0
40
1
4
Order By: Relevance
“…A c c e p t e d M a n u s c r i p t 3 Aldosterone, the endogenous mineralocorticoid in humans, was first isolated in 1953 as the last of the steroid hormones (Simpson et al, 1954). In the early years, the main focus of research lay on the long-term effects of aldosterone on sodium-potassium homeostasis and regulation of blood pressure in so called mineralocorticoid target organs like kidney, colon and salivary glands.…”
Section: Page 3 Of 28mentioning
confidence: 99%
“…A c c e p t e d M a n u s c r i p t 3 Aldosterone, the endogenous mineralocorticoid in humans, was first isolated in 1953 as the last of the steroid hormones (Simpson et al, 1954). In the early years, the main focus of research lay on the long-term effects of aldosterone on sodium-potassium homeostasis and regulation of blood pressure in so called mineralocorticoid target organs like kidney, colon and salivary glands.…”
Section: Page 3 Of 28mentioning
confidence: 99%
“…T he sodium homeostasis regulatory hormone aldosterone was first identified in 1953 (1). Early studies on the biochemical mechanism of its action were reviewed by Edelman and Fimognari (2).…”
mentioning
confidence: 99%
“…In 1952 Tait et al [85] reported the sodiumretaining effect of an unidentified adrenal extract; and in 1953 Simpson et al [78] described the crystallization of this sub stance. Initially named sodium-retaining corticoid by Luetscher and co-workers [54,56] and electrocortin by Simpson et al [77], this hormone was renamed aldosterone when its structure was determined in 1954 [79].…”
Section: Early Studies: 1950-1956mentioning
confidence: 99%